Association of emotion recognition ability and interpersonal emotional competence in anorexia nervosa: A study with a multimodal dynamic task. Issue 2 (14th November 2022) - Martini, Matteo; Marzola, Enrica; Musso, Maria; Brustolin, Annalisa; Abbate‐Daga, Giovanni
Abstract: Objective: Interpersonal difficulties are evidenced in Anorexia Nervosa (AN) and are thought to contribute to disease onset and maintenance, however, research in the framework of emotional competence is currently limited. Previous studies have often only used static images for emotion recognition tasks, and evidence is lacking on the relationships between performance‐based emotional abilities and self‐reported intra‐ and interpersonal emotional traits. This study aimed to test multimodal dynamic emotion recognition ability in AN and analyze its correlation with the psychometric scores of self‐ and other‐related emotional competence. Method: A total of 268 participants (128 individuals with AN and 140 healthy controls) completed the Geneva Emotion Recognition Test, the Profile of Emotional Competence, the Reading the Mind in the Eyes Test, and measures of general and eating psychopathology. Scores were compared between the two groups. Linear mixed effects models were utilized to examine the relationship between emotion recognition ability and self‐reported measures and clinical variables. Results: Individuals with AN showed significantly poorer recognition of emotions of both negative and positive valence and significantly lower scores in all emotional competence dimensions. Beside emotion type and group, linear mixed models evidenced significant effects of interpersonal comprehension on emotion recognition ability. Discussion: Individuals with AN show impairment in multimodal emotion recognition and report their difficulties accordingly. Notably, among all emotional competence dimensions, interpersonal comprehension emerges as a significant correlate to emotion recognition in others, and could represent a specific area of intervention in the treatment of individuals with AN. Public Significance: In this study, we evidence that the ability to recognize the emotions displayed by others is related to the level of interpersonal emotional competence reported by individuals with anorexia nervosa. This result helps in understanding the social impairments in people with anorexia nervosa and could contribute to advancements in the application of the training of emotional competence in the treatment of this disorder.